2016
DOI: 10.1063/1.4945395
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magnetocaloric properties of quasi-one-dimensional Ising spin chain CoV2O6

Abstract: We have investigated the magnetic and magnetocaloric properties of antiferromagnetic Ising spin chain CoV 2 O 6 by magnetization and heat capacity measurements. Both monoclinic α-CoV 2 O 6 and triclinic γ-CoV 2 O 6 exhibit field-induced metamagnetic transition from antiferromagnetic to ferromagnetic state via an intermediate ferrimagnetic state with 1/3 magnetization plateau. Due to this field-induced metamagnetic transition, these systems show large conventional as well as inverse magnetocaloric effects. In α… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
5
22
0
Order By: Relevance
“…This state-which emerges also in DMC simulations-gives rise simultaneously to both Bragglike and structured diffuse magnetic scattering, with the Bragg arXiv:1605.02575v1 [cond-mat.dis-nn] 9 May 2016 intensities indistinguishable from those calculated from the multiple-moment models suggested in previous Rietveld studies. The existence of a well-defined 1D state in Tb(HCOO) 3 distinguishes this system from other spin-chain triangular antiferromagnets such as Ca 3 Co 2 O 6 [8,17], CsNiF 3 [29,30] and CoV 2 O 6 [16] and suggests its low-temperature physics may provide a long-sought-after experimental approximant to "true" 1D magnetism.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This state-which emerges also in DMC simulations-gives rise simultaneously to both Bragglike and structured diffuse magnetic scattering, with the Bragg arXiv:1605.02575v1 [cond-mat.dis-nn] 9 May 2016 intensities indistinguishable from those calculated from the multiple-moment models suggested in previous Rietveld studies. The existence of a well-defined 1D state in Tb(HCOO) 3 distinguishes this system from other spin-chain triangular antiferromagnets such as Ca 3 Co 2 O 6 [8,17], CsNiF 3 [29,30] and CoV 2 O 6 [16] and suggests its low-temperature physics may provide a long-sought-after experimental approximant to "true" 1D magnetism.…”
mentioning
confidence: 89%
“…Although the much-studied Ca 3 Co 2 O 6 is conceptually similar to Tb(HCOO) 3 , the key distinction between the two is the orderof-magnitude difference in J /J ⊥ values that stabilises the intermediate-order state in the latter [17]. Nevertheless, as is the case for Ca 3 Co 2 O 6 , Tb(HCOO) 3 is likely to show anomalous response to applied magnetic field; indeed magnetisation plateaux may explain its high performance as a magnetocaloric material [16,25]. From a materials design perspective, the 1D behaviour of Tb(HCOO) 3 is a direct consequence of the underlying MOF architecture.…”
mentioning
confidence: 99%
“…[36,37] It has 1D ferromagnetic intrachain correlations and weaker interchain antiferromagnetic interactions, and at low temperatures orders into longitudinal amplitude-modulated spin-density wave (SDW) propagating along the c-axis. α-CoV 2 O 6 , a 1D Ising ferromagnet, [38] undergoes transitions into different phases under variable applied fields. Studies of this material also showed that it was an excellent magnetocaloric, within it's operating temperature, with a steep magnetisation curve as a result of overcoming the antiferromagnetic interchain correlations into a ferromagnetic state.…”
Section: (A) Frustrated Magnetism and Magnetic Systemsmentioning
confidence: 99%
“…In this Brief Report we discuss the multi-step behavior in CoV 2 O 6 revealed in Ref. [12] and thoroughly investigated recently [13]. This compound crystallizes in the two allotropic forms [12]: the branneritelike monoclinic structure with the space group C2/m which is schemati- * Electronic address: yu˙kudasov@yahoo.com [14].…”
mentioning
confidence: 99%